ISLAMISASI PENDIDIKAN DI SEKOLAH: Sebuah Harapan dan Tantangan - Ridhwan M. Daud (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2011)
The education for Moslem should be based on the Islamic educational philosophy. In fact, nowadays the education tends to follow the western or non-moeslem education style. The factors affecting this among others are: there are some physical and mental colonization which occurred in the whole country which has the majority of moeslem society in the past. Besides, there are some values among moeslem themselves after they are assimilated with other thoughts and culture. Both factors are facing and will be faced by Moslems continuously. This condition is very dangerous for Moslems. To reduce or at least to minimize the danger for Moslems society, one way to solve the problem is through educational Islamization at school. The main contraint is good will from government and society. Besides, the teacher competency is still low and also lack of proper references. The islamization process will work well with the support from many people.